Study on the performance of underground XLPE cables in service based on tan delta and capacitance parameters - Ponniran, Asmarashid (2005)
By the rapid of urban growth, it is impossible to accommodate the number and size of feeder required for distribution using the overhead line system approach. As an alternative the underground cables becomes more increasingly necessary to replace some of the overhead line for power transmission and distribution. Because of that reason, underground XLPE cables are the most popular for the underground systems. Performance of underground cables in service is being critical because of ageing mechanisms influences. There are many suitable techniques can be used to evaluate performance of aged and unaged underground cables. One of the techniques is based on tan delta and capacitance parameters of underground cables. This study only focuses on underground XLPE cables, which are voltage rated at11kV and 22kV for 1-core and 3-cores types. By using Tettex Instruments – Schering Bridge Model 2816, tan delta and capacitance data of XLPE underground cables are obtained. Tan delta and capacitance measurements were performed at ambient temperature (26.6oC) and at power frequency (50 Hz). From these analyses, show that tan delta values will be increased proportional with aging time of cables in service. Aging mechanisms are contributes these deteriorations of cables in service and consequently values of tan delta are increased with aging time of cable. Meanwhile, form capacitance analysis, the values of capacitance will be increased when contaminants, protrusions and voids are affected cables insulation and when moisture enters inside underground cable systems